(3GJaGbjI HhOGHSJ decGaMI LQGFe GdeYdheGJjI eYdbG YdjgG (B/s - (3YHO GdYGd, gdGdj YHO GddGg CMeOs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2011)
(3MQU eLdS ChQHG Ydi GdJUOj ddGSJNOGe ZjQ GdeTQhY ddMGSHGJ hTHcGJ GdeYdheGJ, hJLdi Pdc aj GJaGbjI HhOGHSJ GdeTGQ EdjgG GdehbYI aj (B23 (3fhaeHQ (B2001 (3GdeJYdbI HGdELQGe Gdchfj HeYfi GdELQGe GdeYdheGJj Ch GdLQGFe GdeYdheGJjI, EjeGfG ef GdOhd GdCYVGA aj gPG GdeLdS hGdOhd GdCNQi GdehbYI Ydi gPg GdEJaGbjI HGdJZjQGJ GdYejbI GdJj MOKJ HSHH GdQbejI hGdJbGQH hGdYhdeI GdeSJeQI, aef NdGd GdGJUGdGJ HNOeGJ GdGJUGdGJ hGdeYdheGJ jSJWjY GdeSJNOehf GUWfGY aVGA LOjO jSei (B"(3GdaVGA GdeYdheGJj(B" (3GdPj jSJYed CSGSG dCZQGV TQYjI, hdcf jecf Cf jNVY dShA GdGSJNOGe EP gfGc GMJeGd dGSJNOGe THcGJ GdMGSH hGdeYdheGJ GdEdcJQhfjI aj GQJcGH GYeGd ELQGejI, hYdi Pdc jLH Ydi GdbGfhf GdLfGFj Cf jMGaX Ydi ehGcHJg dgPg GdJWhQGJ GdJcfhdhLjI GdJj JbOe aQUG hGSYI dGSGAI GSJNOGe EecGfjGJ GdaVGA GdeYdheGJj, hCf jYed Ydi QOY gPg GdCaYGd GdELQGejI, eY JWjHb GdSdWGJ GdbSQjI GdebQQI aj HjFI JcfhdhLjG GdeYdheGJ, hJJchf gPg GdEJaGbjI ef KeGfj hCQHYjf eGOI jgefG efG GdehGO ef (B1-35 (3GdJj fhO Cf fbOegG ddeTQY GdeUQj Ydi hLg GdNUhU hGdeTQhY GdYQHj Ydi GdhLg GdYehe cfehPL jMJPi Hg aj eLGd ecGaMI LQGFe GdeYdheGJjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B439-441.s
Keywords: (3GJaGbjI HhOGHSJs -- (23 (3fhaeHQ (B2001)s; (3GdLQGFe GdMGShHjI (B((3bGfhf Ohdj(B)s -- (3eYGgOGJs